Analysis of the integrated logistic system on example of transport forwarding firm work - Очеретна, Валентина Валеріївна (Technology audit and production reserves, 2014)
The construction of integrated logistics system on the example of transport forwarding firm work is investigated. This system will contribute to the optimal organization of transportation of goods and services. The improving of efficiency of transport forwarding firm and its industrial and commercial activity that will lead to increased competitiveness of forwarding company by attracting additional volumes of cargo will be provided due to this organization. A systematic approach and methods of system analysis, statistical methods of information processing, comparative analysis, logic modeling are applied for solving these problems. Thus, the logistics system is a set of logistic chains of forwarding companies, joint by logistics agreements. The construction of a well-functioning integrated transport and logistics intermodal transport system will contribute to the optimal organization of transportation within the system, thereby ensuring its competitiveness by attracting of additional volumes of transit cargo.